Aplicación de las técnicas del diseño gráfico e industrial a una propuesta de señalética interior y exterior, equipamiento urbano, imagen corporativa, web 2.0 y ecodiseño para el acuario de Valdivia - Astudillo Bastidas, María José (2014)
Valdivia Aquarium is a community agency that opened to the public on July 16, 1997. It is a rescue center for confiscated animals, sick and collected species arriving at the facility, from various parts of the Costa carried by tourists and fishermen. Today Valdivia Aquarium, has seen the need of redesigning your infrastructure, urban (exterior and interior), signage and eco design, in order to reflect a better image, and reconstruct the identity of Valdivia. It has the financial means the Ministry of Tourism has approved the redesign of urban interior and exterior signage of the current institution. This project aims to apply the techniques presented in Graphic Design and Industrial to all interior and exterior signage, equipment urban, corporate image, Web 2.0 and ecodesign for Valdivia Aquarium. This project is to identify the techniques of Graphic and Industrial Design in order to achieve an improvement in the aquarium of Valdivia with a proposed indoor and outdoor signage, street furniture, corporate image, Web 2.0. and Ecodesign for Valdivia Aquarium.